Accessing energy efficiency potential in the Malaysian Universities: the literature review / Muhammad Hilmi Dzulkefli, Nur Azfahani Ahmad and Haryati Mohd Isa - Dzulkefli, Muhammad Hilmi; Nur Azfahani Ahmad, Nur Azfahani; Mohd Isa, Haryati (2018)
Energy efficiency has become one of the essential elements in managing energy consumption for universities. In assessing energy efficiency, a few processes of energy audit, energy performance of the buildings and energy management need to be monitored and areas which have the potential for energy savings should be identified. The purpose of this paper is to explore the literature review that focus on the energy audit processes conducted in the Malaysian universities and to identify the best practice that can improve energy consumption of the universities. The initial energy audit framework of the Malaysian universities will be explored in the literature in order to acquire related information on energy efficiency, namely from electrical appliances and lightings systems in order to understand the relationship of these factors with the use of energy. The significant practices in energy audit can help to save electricity by comparing the energy implementation process of Malaysian universities. Through the investigation of energy consumption behavior and the number of electrical appliances, machinery and buildings activities, it will affect the energy consumption that can allow energy-efficiency in building. The Building Energy Index (BEI) will be used as an indicator and combined with the application of building energy simulation software to obtain solution and possible improvement of energy consumption during energy audit implementation. The exploration of literature will be used as a guideline for universities that consume high energy in order to control the excessive energy usage and to achieve energy efficiency for the building.